Motivation for Motion: Designing, Implementing, and Assessing an Intervention to Enhance Physical Activity Motivation in Substance Use Disorder Recovery - Thal, Sascha Bodo (Curtin University, 2025)
This PhD explores a motivational intervention to enhance physical activity (PA) participation in residential substance use disorder (SUD) treatment. A systematic review identified promising behaviour change techniques (BCTs), followed by qualitative studies informing a 12-session motivational interviewing-based intervention. Pilot results showed no significant PA behaviour changes but improvements in motivation and affect. Findings highlight the intervention’s feasibility, acceptability, and potential to enhance PA motivation, supporting future research and real-world applications in SUD treatment settings.